Reflections and experiences on interculturality and ethics in the patient approach - Guzmán-Barrón, Rosanna Morales (2022)
The concept of interculturality is used extensively and  recurrently in both foreign and national meetings and scientific publications, both foreign and national. It is important to value concepts that are  intertwined with the field of health. health. In this regard,  we reflect and analyze the fact that Peru is a  pluricultural country, with populations that belong to country, with populations that belong to different ethnic- cultural groups and speak different different ethnic-cultural groups and speak different languages. At the same time, public at the same time, public services are oriented to satisfy the needs of all Peruvians. Peruvians, which is why they must take into account the ethnic and cultural diversity of the population. and cultural diversity of the population. Therefore, public services that do not  incorporate cultural perspectives of the population generate gaps that discourage people that discourage the population from seeking the same services.